2002
DOI: 10.1046/j.1365-2648.2002.02159.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nurse‐led counselling service on quality of life in patients with inflammatory bowel disease

Abstract: Health related quality of life can be improved over 6 months by provision of a nurse led counselling service but the effects are not sustained for 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 17 publications
4
45
0
3
Order By: Relevance
“…Of these, a further 32 were excluded for various reasons leaving 14 studies eligible for data extraction. [23][24][25][26][27][28][29][30][31][32][33][40][41][42] Agreement between reviewers for eligibility assessment was excellent (Kappa statistic = 0.91). Detailed study characteristics are provided in Table 1, and risk of bias across all studies is reported in page 1 of the webappendix.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, a further 32 were excluded for various reasons leaving 14 studies eligible for data extraction. [23][24][25][26][27][28][29][30][31][32][33][40][41][42] Agreement between reviewers for eligibility assessment was excellent (Kappa statistic = 0.91). Detailed study characteristics are provided in Table 1, and risk of bias across all studies is reported in page 1 of the webappendix.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27][28][29]32,33,[40][41][42] . Four of these presented data in patients with CD, 25,32,40,42 four in patients with UC, 27,28,40,41 and five in patients with IBD. 23,24,26,29,33 Results from all analyses in patients with quiescent IBD are summarised in Table 2.…”
Section: Quality Of Life In Patients With Quiescent Ibdmentioning
confidence: 99%
See 3 more Smart Citations